2016
DOI: 10.1017/s1751731116000367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adsorbants on in vitro biohydrogenation of 22:6n-3 by mixed cultures of rumen microorganisms

Abstract: Studies on microbial biohydrogenation of fatty acids in the rumen are of importance as this process lowers the availability of nutritionally beneficial unsaturated fatty acids for incorporation into meat and milk but also might result in the accumulation of biologically active intermediates. The impact was studied of adsorption of 22:6n-3 (DHA) to particulate material on its disappearance during 24 h in vitro batch incubations with rumen inoculum. Four adsorbants were used in two doses (1 and 5 mg/ml of mucin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…Very long chain n-3 PUFA from marine lipids are extensively metabolized in the rumen, but the intermediates formed and the pathways involved remain largely unknown (Kairenius et al, 2011;Escobar et al, 2016). We conducted a direct comparison of in vitro ruminal -∆8,13,16,19 + 9,13,16,19 22:4 trans-8,cis-13,cis-16,cis-19 + trans-9, cis-13,cis-16, cis-19 -∆11,14,19 + 13,16,19 + 13,16,19 22:3 trans-11,trans-14,cis-19 + trans-13,cis-16, trans-19 + cis-13,cis-16,trans-19 -∆11,16,19 + 13,16,19 + 13,16,19 22:3 cis-11,cis-16,cis-19 + trans-13,cis-16,cis-19 + cis-13,trans-16,cis-19 Based on the relatively well known BH of linoleic and α-linolenic acids (Lee and Jenkins, 2011;Alves and Bessa, 2014;Honkanen et al, 2016), it was expected that the isomerization of a cis double bond would also represent the first major step in the ruminal metabolism of other polyenoic FA with different chain length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very long chain n-3 PUFA from marine lipids are extensively metabolized in the rumen, but the intermediates formed and the pathways involved remain largely unknown (Kairenius et al, 2011;Escobar et al, 2016). We conducted a direct comparison of in vitro ruminal -∆8,13,16,19 + 9,13,16,19 22:4 trans-8,cis-13,cis-16,cis-19 + trans-9, cis-13,cis-16, cis-19 -∆11,14,19 + 13,16,19 + 13,16,19 22:3 trans-11,trans-14,cis-19 + trans-13,cis-16, trans-19 + cis-13,cis-16,trans-19 -∆11,16,19 + 13,16,19 + 13,16,19 22:3 cis-11,cis-16,cis-19 + trans-13,cis-16,cis-19 + cis-13,trans-16,cis-19 Based on the relatively well known BH of linoleic and α-linolenic acids (Lee and Jenkins, 2011;Alves and Bessa, 2014;Honkanen et al, 2016), it was expected that the isomerization of a cis double bond would also represent the first major step in the ruminal metabolism of other polyenoic FA with different chain length.…”
Section: Discussionmentioning
confidence: 99%
“…The transient nature of conjugated 18-carbon FA has not precluded their usual detection in the ruminal digesta (Wallace et al, 2007;Lee and Jenkins, 2011;Honkanen et al, 2016). Nevertheless, detailed chromatographic analyses have failed to identify conjugated 20-and 22-carbon FA of ruminal origin in dairy cows, ewes, and goats fed marine lipids (Kairenius et al, 2011;Toral et al, 2012Toral et al, , 2016 or in most in vitro incubations with DHA (Escobar et al, 2016;Jeyanathan et al, 2016). Compared with other data from mixed cultures of rumen microorganisms (Aldai et al, 2012;Vlaeminck et al, 2014;Escobar et al, 2016), the relatively high dose of PUFA in our trial (2% DM of the substrate) would have slowed down the BH process, facilitating the detection of initial intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to trans 18-carbon biohydrogenation intermediates, MFD induced by the supplementation of marine lipids is associated with the formation, ruminal accumulation and outflow of biohydrogenation intermediates with 20 or 22 carbon atoms. Although the biohydrogenation pathways of 20:5n-3 or 22:6n-3 are far from being elucidated, numerous intermediates have been identified recently both under in vivo and in vitro conditions, in cows and small ruminants and with mixed, as well as pure, rumen bacteria (Escobar et al, 2016;Jeyanathan et al, 2016;Aldai et al, 2018;Kairenius et al, 2018;Toral et al, 2018a). From the biohydrogenation pathways of 18:2n-6 and 18:3n-3, isomerization and migration of a cis double bond resulting in the production of monoconjugated 20:5 and 22:6 would have been expected.…”
Section: Biohydrogenation Intermediates Associated With Mfdmentioning
confidence: 99%
“…In accordance with our findings, Toral et al [ 45 ] observed a several-fold higher transfer efficiency of DPA than that of DHA in algae-fed ewes. Unfortunately, the literature is lacking for enzymes that may regulate the DHA hydrogenation pathway in the rumen [ 46 ], while the degradation of DHA and DPA to other isomers is also hard to study in in vivo trials due to their short lifetime [ 47 ].…”
Section: Discussionmentioning
confidence: 99%